Beyond the crisis. Horizons from a decolonial perspective - Germaná, César (2019)
This article argues on the reflections of Anibal Quijano, which have been focused on conceiving a new approach to understand the problems of Latin America. Among the different subjects to be explored within his vast theoretical production, we will examine three core ideas that remain central to his concerns and that are fundamental to explain the forms of organization and the possibilities of transformation of the current social order. First, the notion of pattern of power; secondly, the nature of the crisis of the colonial/modern pattern of power; and third, the tendencies towards decoloniality of power and the future historical options.